Pengaruh Blended Learning Berbantuan Google Classroom terhadap Kemampuan Berpikir Kritis Peserta Didik Kelas X SMA Negeri 1 Pandawai - Huki, Yohanis; Bano, Vidriana Oktoviana; Enda, Riwa Rambu Hada (Jurnal Kridatama Sains dan Teknologi, 2024)
During the Covid-19 pandemic, learning became ineffective, students felt bored and did not understand the material provided and teachers still used active lectures duringmeetings offline. This has an impact on students' critical thinking skills. This study aims to determine the effect of Blended Learning -assisted Google Classroom on students' critical thinking skills on protist material. This type of research is experimental research using Quasi Experimental Design. The design used is the Noneequivalent Pretest-posttest Control Group Design. Data collection techniques used in this study consisted of tests, questionnaires, and documentation. The population in this study were all students of SMA Negeri I Pandawai. The sampling technique in this study used purposive sampling. The research sample consisted of 2 classes, one class as the experimental class (X IPA I) and the control class (X IPA 2). Based on the results of thet test analysis independently, critical thinking skills show the value of Sig.(2tailed) 0.025 <0.05 thenH0 is rejected and H1 accepted. This means that there is an effect of themodel Blended Learning assisted Google Classroom- on the critical thinking skills of class X science students on protist material at SMA Negeri I Pandawai